PRELIMINARY STUDY ON THE DISTRIBUTION OF THE AEROBIC HETEROTROPHIC BACTERIA AND THE MICROBIAL INDICATORS IN JAKARTA BAY - Thayib, Soeminarti S.; Soehadi, Flor (Marine Research in Indonesia, 1977)
The distribution of heterotrophic bacteria and microbial indicators in the Jakarta Bay were studied. Higher frequency of occurrences of the total coliform were observed in water samples collected near rivermouths or in the vicinity of islands. Lower frequency of occurrences of total coliform were obtained from samples collected from the far northern side of the Bay. The isolated strains belong to the genera Achromobacter, Vibrio, Flavobacteria, Micrococcus and coliforms. Micrococcus and coliforms were mostly obtained from samples collected at stations which are suspected to be highly influenced by human activities. The presence of Vibrio parahaemolyticus-like organisms were also determined. Occurrences of the genera varied unpredictably but were mostly within the six genera mentioned.